2015
DOI: 10.1186/1472-6831-15-7
|View full text |Cite
|
Sign up to set email alerts
|

Pocket depth and bleeding on probing and their associations with dental, lifestyle, socioeconomic and blood variables: a cross-sectional, multicenter feasibility study of the German National Cohort

Abstract: BackgroundTo investigate the periodontal disease status in a multi-center cross-sectional study in Germany. Associations of dental, socio-economic, blood and biomedical variables with periodontal outcome parameters were evaluated.MethodsFrom 4 different centers N = 311 persons were included, drawn randomly from the registration offices. Maximal pocket depth (PD) was used as primary indicator for periodontitis. It was classified as: no/mild ≤3 mm, moderate 4-5 mm, severe ≥6 mm. Associations between socioeconomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
43
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 54 publications
6
43
3
1
Order By: Relevance
“…BOP and PD were significantly higher in both groups at the end of the follow-up period, although there was no significant difference between the two groups regarding both parameters. However, the mean pocket depth for each group was less than 3mm, which remains within the normal range for healthy periodontium 30 . This slight decline in periodontal condition is probably a normal consequence of the presence of fixed restoration on the abutment teeth.…”
Section: Discussionsupporting
confidence: 56%
“…BOP and PD were significantly higher in both groups at the end of the follow-up period, although there was no significant difference between the two groups regarding both parameters. However, the mean pocket depth for each group was less than 3mm, which remains within the normal range for healthy periodontium 30 . This slight decline in periodontal condition is probably a normal consequence of the presence of fixed restoration on the abutment teeth.…”
Section: Discussionsupporting
confidence: 56%
“…A dental caries is a chronic bacterial infection; studies showed that hemoglobin, iron, and ferritin levels increased when dental caries was cured (27). Another study suggested that erythrocyte levels were not affected by poor oral health (31). The present study suggested that the erythrocyte, hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, red cell distribution width, and iron and ferritin levels were similar in both the groups.…”
Section: Discussionsupporting
confidence: 56%
“…Even though some evidence has been provided for antagonism between Aa and Sm , this has only been observed in vitro . While the findings of later studies did not support a negative relationship between juvenile periodontitis and caries, studies continue to purport a lower caries experience in “aggressive” periodontitis cases than in cases of “chronic” periodontitis …”
Section: Introductionmentioning
confidence: 96%